Enabling relay selection in non-orthogonal multiple access networks: direct and relaying mode - Dinh-Thuan Do; Minh-Sang V. Nguyen (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this paper, we consider downlink non-orthogonal multiple access (NOMA) in which the relay selection (RS) scheme is enabled for cooperative networks. In particular, we investigate impact of the number of relays on system performance in term of outage probability. The main factors affecting on cooperative NOMA performance are fixed power allocations coefficients and the number of relay. This paper also indicate performance gap of the outage probabilities among two users the context of NOMA. To exhibit the exactness of derived formula, we match related results between simulation and analytical methods. Numerical results confirms that cooperative NOMA networks benefit from increasing the number of relay.